The relationship of cigarette addiction, smartphone addiction and self-control of men's dormitory students - Purnomo, Andreas Wisnu adi; Loekmono, J.T. Lobby (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
This study aims to determine whether there is a significant relationship between cigarette addiction, simultaneous smartphone addiction and self-control. The subjects who became respondents were students who live in the male dormitory of Satya Wacana Christian University, totalling 109 students as the population. The sampling technique chosen was purposive sampling with the criteria of students who were active smokers and were involved in using smartphones. The research method used is correlational quantitative. The sample consisted of 33 students. The analysis technique used is the multiple correlation formula. Based on the results of various correlation analyzes, the R-value is -0.350 in the opposite direction. For comparison, the Fcount value is found to be 2.128 and the F table with a significant 5% of 4,130. In other words, Fcount <Ftable, which means there is no significant relationship. The results of this study found that there was no significant relationship between cigarette addiction, simultaneous smartphone addiction and self-control.